Hardware-based application of data security system using general modified secured diamond encoding embedding approach for enhancing imperceptibility and authentication - Moon, Sunil K.; Raut, Rajshree D. (Multimedia tools and applications, 2019)
As today’s world are switching to the digital media through the Internet and multimedia tools like Facebook, YouTube, Twitter and WhatsApp which consists of a number of videos, hence it always better to take urgent problems of such digitally transmitted video in terms of information security. The current video steganography approach is not so effective for imperceptibility, robustness, security of hidden secret data, embedding capacity and very good visual recovery of a secret as well as original data. Hence, to maintain the balance between these issues is another big challenge. This work employs a novel and efficient Field Programmable Gate Array (FPGA) implementation of audio, video crypto steganography using General Modified Secured Diamond Encoding (GMSDE) scheme. The new proposed scheme is based on Diamond Encoding (DE), Exploiting Modification Direction (EMD) and Adaptive Pixel Pairing Matching (APPM) algorithms called as General Modified Secured Diamond Encoding (GMSDE). The DE method is always used for k > 1 which produces distortion, less embedding capacity and security of hidden data. The GMSDE scheme changed the Diamond Characteristic Value (DCV) to conceal more than one secret bit vertically and horizontally to create a modified diamond shape of secret data which is equal to log 2 (2 x 2 + 6 x + 5) - ary and produces the conceal capacity of 1.16 to 4.82 bpp for the values of x = 0 to 25 where x is the embedding parameter. Experimental results confirm that the conceal capacity measured by bit per pixel (bpp), security of hidden secret data, very good visual recovery of both original and secret data, Cross-Correlation (CC) and Peak Signal to Noise Ratio (PSNR) values are better than existing approaches. Further through many attacks on stego video during transmission using forensic detection approach, the imperceptibility, security of hidden data and robustness is increased for secure communication.